Multidimensional endotypes of asthma: topological data analysis of cross-sectional clinical, pathological, and immunological data. (26th February 2015) - Hinks, Timothy; Zhou, Xiaoying; Staples, Karl; Dimitrov, Borislav; Manta, Alexander; Petrossian, Tanya; Lum, Pek; Smith, Caroline; Ward, Jon; Howarth, Peter; Walls, Andrew; Gadola, Stephan D; et al.
Abstract: Background: Incomplete understanding of mechanisms and clinicopathobiological heterogeneity in asthma hinders research progress. Pathogenic roles for T-helper-type 17 (Th17) cells and invariant T cells implied by murine data have yet to be assessed in man. We aimed to investigate the role of Th17 and mucosal associated invariant T (MAIT) cells in airway inflammation; to characterise associations between diverse clinical and immunological features of asthma; and to identify novel multidimensional asthma endotypes. Methods: In this single-centre, cross-sectional observational study in the UK, we assessed volunteers with mild-to-severe asthma and healthy non-atopic controls using clinical and physiological assessment and immunological sampling of blood, induced sputum, endobronchial biopsy, and bronchoalveolar lavage for flow cytometry and multiplex-electrochemiluminescence assays. Primary outcomes were changes in frequencies of Th17 and MAIT cells between health and asthma using Mann-Whitney U tests and the Jonckheere-Terpstra test (linear trend across ranked groups). The study had 80% power to detect 60% differences in T-cell frequencies at p<0·05. Bayesian Network Analysis (BNA) was used to explore associations between parameters. Topological Data Analysis (TDA) was used to identify multidimensional endotypes. The study had local research ethics approval. All participants provided informed consent. Findings: Participants were 84 male and female volunteers (60 with mild-to-severe asthma and 24 healthy, non-atopic controls) aged 18–70 years recruited from clinics and research cohorts. Th17 cells and γδ17 cells were not associated with asthma, even in severe neutrophilic forms. MAIT-cell frequencies were strikingly reduced in asthma compared with health (median frequency in blood 0·9% of CD3+ cells [IQR 0·3–1·8] in asthma vs 1·6 [1·2–2·6] in health, p=0·005; in sputum 1·1 [0·7–2·0] vs 1·8 [1·6–2·3], p=0·002; and in biopsy samples 1·3 [0·7–2·3] vs 3·9% [1·3–5·3%], p=0·02), especially in severe asthma where BAL regulatory T cells were also reduced compared with those in health (4·4, 3·1–6·1, vs 8·1, 5·6–10; p=0·02). BNA and TDA identified six novel clinicopathobiological clusters of underlying disease mechanisms, with elevated mast cell mediators tryptase (p<0·0001), chymase (p=0·02), and carboxypeptidase A3 (p=0·02) in severe asthma. Interpretation: This study suggests that Th17 cells do not have a major pathogenic role in human asthma. We describe a novel deficiency of MAIT cells in severe asthma. We also provide proof of concept for application of TDA to identification of multidimensional clinicopathobiological endotypes. Endotypes will require validation in further cohorts. Funding: Wellcome Trust.